Properties, processing and applications of glass and rare earth-doped glasses for optical fibres - Hewak, Dan (IEE, INSPEC, 1998)
Annotation An authoritative, encyclopedic reference source for researchers and engineers interested in R & D into optical fibers.
Keywords: Glass fibers.; Optical fibers.; elektronické knihy; electronic books